Idaho State Building, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Idaho Building. Printed on verso: 65. The Idaho State Building is beautifully situated upon Dome Circle. An air of welcome and comfort pervades. In the wings are displays showing the state's abundance and prosperity. 1909. The Alaska-Yukon-Pacific Exposition. Official Photograph. Published by Robert A. Reid. 488 Arcade. Made in Seattle. PH Coll 777 Reid.65 (See also PH Coll 78.23) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number